DDB2 represses epithelial-to-mesenchymal transition and sensitizes pancreatic ductal adenocarcinoma cells to chemotherapy - Dardare, Julie; Witz, Andréa; Betz, Margaux; Francois, Aurélie; Meras, Morgane; Lamy, Laureline; Lambert, Aurélien; Grandemange, Stéphanie; Husson, Marie; Rouyer, Marie; Demange, Jessica; Merlin, Jean-Louis; et al. (Frontiers in Oncology, 2022)
Damage specific DNA binding protein 2 (DDB2) is an UV-indiced DNA damage recognition factor and regulator of cancer development and progression. DDB2 has dual roles in several cancers, either as an oncogene or as a tumor suppressor gene, depending on cancer localization. Here, we investigated the unresolved role of DDB2 in pancreatic ductal adenocarcinoma (PDAC). Using publicly available data, we found reduced expression level of DDB2 in PDAC tissues and DDB2-low levels were correlated to shorter disease-free survival in PDAC patients. We developed two PDAC cell models with modified DDB2 expression. DDB2 overexpression increased expression of E-cadherin epithelial marker, and decreased levels of N-cadherin mesenchymal marker. Conversely, we observed opposite effects in DDB2 repression and enhanced transcription of SNAIL, ZEB1, and TWIST EMT transcription factors (EMT-TFs). Study of migration and invasion revealed that these properties were negatively correlated with DDB2 expression in both cell models. We determined sensitivity to chemotherapies and found that DDB2 overexpression sensitized cells to 5-fluorouracil, oxaliplatin and gemcitabine. Our study highlights the potential tumor suppressive-effects of DDB2 on PDAC progression. DDB2 could thus represent a promising therapeutic target or biomarker for defining prognosis and predicting chemotherapy response in patients with PDAC.